2016
DOI: 10.12664/mycobiota.2016.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Myxomycetes in Turkey – a checklist

Abstract: Th is checklist contains 252 species of myxomycetes recognized as occurring in Turkey. Th e names are arranged alphabetically. For each species, references are cited. An index of synonyms, based on literature records from Turkey, is appended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 4 publications
(38 reference statements)
2
27
0
2
Order By: Relevance
“…Previously, 21 species of Licea were recorded in Turkey (Sesli et al, 2016). In this paper, we reported a new record L. pescadorensis.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previously, 21 species of Licea were recorded in Turkey (Sesli et al, 2016). In this paper, we reported a new record L. pescadorensis.…”
Section: Resultsmentioning
confidence: 83%
“…Licea has got 21 species (Sesli et al, 2016). Licea genera includes species with plasmodiocarpic to sporocarpic sessile or stipitate sporophores.…”
Section: And In Turkeymentioning
confidence: 99%
“…Light microscopy is used to determine the presence of capillitium, pseudo-capillitium and columella, and if present, their shape and dimensions, ornamentation of the threads in the capillitium, branching form, the presence of free or stem-connected nature of the columella, the features of the pseudo-capillitium, shape, color, and size of the spores, and spore ornamentations in detail ( Figure 1). The material, whose properties were determined, were identified based on the studies by Thind, 8 Farr, 9 Stephenson & Stempen, 4 Neubert et al, 10 Ergul & Akgul, 11 and Sesli et al 12 The identified 5g samples were extracted in Soxhlet extractor for about 6 hours at 50 0 C with ethanol (EtOH), methanol (MeOH) and dichloromethane (DCM) (Gerhardt EV 14). The obtained extracts were concentrated with a rotary evaporator (Heidolph Laborota 4000 Rotary Evaporator) ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In our study it was isolated on the bark of Platanus orientalis. This species has only been reported a few times in Turkey (13). It could be found on rotting plant refused and dead leaves occasionally in bark culture and one of the commonest myxomycetes that can be found in Europe (29).…”
Section: Licealesmentioning
confidence: 99%
“…In 1993 C. Ergül (12) reported 61 taxon were reported in the Marmara region in the first doctorate thesis in Turkey on myxomycetes. The number of myxomycetes species reported in Turkey so far is 252 reported in different parts of the Country (13). Touray and Ergul.…”
Section: Introductionmentioning
confidence: 99%